Work Hours Mismatch - Marta Lachowska; Alexandre Mas; Raffaele Saggio; Stephen A. Woodbury (Institute of Labor Economics (IZA), 2024)
Using a revealed preference approach applied to administrative data from Washington we document that workers have limited discretion over hours at a given employer, there is substantial mismatch between workers who prefer long hours and employers that provide short hours, and hour constraints are prevalent. Voluntary job transitions imply that a ratio of the marginal rate of substitution of earnings for hours to the wage rate is on the order of 0.5-0.6 for prime-age workers. The average absolute deviation between observed and optimal hours is about 15%, and constraints on hours are particularly acute among low-wage workers. On average, observed hours tend to be less than preferred levels, and workers would require a 12% higher wage with their current employer to be as well off as they would be after moving to an employer offering ideal hours. These findings suggest that hour constraints are an equilibrium feature of the labor market because long-hour jobs are costly to employers.
Keywords: J22; J23; J31; J40; 330; hour constraints; mismatch; sorting; labor supply; willingness to pay; wage premiums; hour policies